SIKAP KONSUMEN TERHADAP KOMODITAS EDIBLE FLOWERS (Suatu Kasus pada IJO Hydro Rooftop Garden and Hydroponic Market) - Etika Larasati; Agriani Hermita Sadeli (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
Floriculture is a potential commodity and is in demand in Indonesia. Edible flowers are one of the consumable floricultural commodities. In Indonesia, the utilization and consumption level of edible flowers is not optimal. In order to maximize the marketing activities of edible flowers, a company must be able to study consumer behavior. Analysis of consumer attitudes is used in this study to determine the tendency of consumers to behave towards edible flower commodities. This study uses a quantitative design and a survey method using a questionnaire instrument. The sample size used was 51 respondents. The method used is a descriptive analysis to analyze respondents' attitudes based on the affective attitude attribute towards edible flower commodities. The results of this study indicate that the majority of respondents' attitudes towards the affective attitude attribute towards edible flower commodities showed good results. The highest affective attitude attribute was in the attribute, which stated that the edible flower commodity was attractive. Meanwhile, the lowest affective attitude attribute is in the attitude attribute 'Important'.